Role of Ferrate(IV) and Ferrate(V) in Activating Ferrate(VI) by Calcium Sulfite for Enhanced Oxidation of Organic Contaminants - Shao, Binbin; Dong, Hongyu; Sun, Bo; Guan, Xiaohong (Environmental science & technology, 2019)
Although the Fe(VI)–sulfite process has shown great potential for the rapid removal of organic contaminants, the major active oxidants (Fe(IV)/Fe(V) versus SO4 •–/•OH) involved in this process are still under debate. By employing sparingly soluble CaSO3 as a slow-releasing source of SO3 2–, this study evaluated the oxidation performance of the Fe(VI)–CaSO3 process and identified the active oxidants involved in this process. The process exhibited efficient oxidation of a variety of compounds, including antibiotics, pharmaceuticals, and pesticides, at rates that were 6.1–173.7-fold faster than those measured for Fe(VI) alone, depending on pH, CaSO3 dosage, and the properties of organic contaminants. Many lines of evidence verified that neither SO4 •– nor •OH was the active species in the Fe(VI)–CaSO3 process. The accelerating effect of CaSO3 was ascribed to the direct generation of Fe(IV)/Fe(V) species from the reaction of Fe(VI) with soluble SO3 2– via one-electron steps as well as the indirect generation of Fe(IV)/Fe(V) species from the self-decay of Fe(VI) and Fe(VI) reaction with H2O2, which could be catalyzed by uncomplexed Fe(III). Besides, the Fe(VI)–CaSO3 process exhibited satisfactory removal of organic contaminants in real water, and inorganic anions showed negligible effects on organic contaminant decomposition in this process. Thus, the Fe(VI)–CaSO3 process with Fe(IV)/Fe(V) as reactive oxidants may be a promising method for abating various micropollutants in water treatment.